Genetic regulation of the intercellular adhesion locus in staphylococci - Cue, David R.; Lei, Mei G.; Lee, Chia (Frontiers in Cellular and Infection Microbiology, 2012)
The formation of biofilms by Staphylococcus aureus and Staphylococcus epidermidis is an important aspect of many staphylococcal infections, most notably endocarditis, osteomyelitis and infections associated with indwelling medical devices. The major constituents of staphylococcal biofilms are polysaccharides, such as poly N-acetyl glucosamine (PIA/PNAG), cell surface and secreted bacterial proteins, and extracellular DNA. The exact composition of biofilms often varies considerably between different strains of staphylococci and between different sites of infection by the same strain. PIA/PNAG is synthesized by the products of four genes, icaADBC, that are encoded in a single operon. A fifth gene, icaR, is a negative regulator of icaADBC. Expression of icaADBC is tightly regulated, but can often be induced in vitro by growing staphylococci in the presence of high salt, high glucose, or ethanol. Regulation of icaADBC is complex and numerous regulatory factors have been implicated in control of icaADBC. Many of these are well known global transcriptional regulatory factors like SarA and sigmaB, whereas other regulators, such as IcaR, seem to affect expression of relatively few genes. Here, we will summarize how various regulatory factors affect the production of PIA/PNAG in staphylococci.